Superparamagnetic polyhemoglobin-tyrosinase nanocapsules: a novel biotherapeutic with enhanced tumor suppression with control by external magnetic field - Zhao, ChenHui; Chang, Thomas Ming Swi (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionOur recent study shows nanobiotherepeutic Polyhemoglobin-Tyrosinase-Nanocapsules (PolyHb-Tyr-Nano) have strong anti-tumor abilities in multiple cancer lines. However, despite their tumor inhibitory potential, some internal tumor sites can be difficult to reach.MethodsIn this paper, based on Chang’s original finding that artificial cells containing magnetic material can be controlled by external magnetic fields, using nanoprecipitation methods, we modified this biotechnological nanotherapeutic with superparamagnetic properties, which shown to be attracted and guided by external magnets.ResultsBy fluorescence microscopy, we show that external magnetic field improved the local deposition of the nanorobotic superparamagnetic PolyHb-Tyr-nano at the tumor microenvironment (TME), significantly preventing their clearance, to stay at the tumor site despite repeated washings. This allowed time for them to enter the tumor cells to act intracellularly. In cell proliferation tests and tumor migration study, their tumor inhibitory action on the four cancer cell lines: Hepa 1-6 liver cancer line, A549 lung cancer line, HeLa cervical cancer line, and MCF7 breast cancer line are also retained effective, a low cell viability and tumor migration was observed. Furthermore, the addition of superparamagnetic property has enhanced the nanocapsules uptake and tumor inhibitory abilities, significantly improved their drug effect on tumor cells. Via cell viability test, PAL assay, oxidative stress detection, and mitochondria membrane potential studies, the PolyHb-Tyr-nano has shown improved tumor killing, by amino acid reduction, reactive oxygen species (ROS) generation, to mitochondria activity reduction in the presence of external magnetic fields.DiscussionOur results showed the efficacy of the nanorobotic superparamagnetic PolyHb-Tyr-nano on anti-tumor effect in multiple cancer lines. This novel nanobiotherapeutic has the potential for future cancer therapy, and can enhance drug localization, targeted delivery, and combination therapies.